Implementation of the National Logistic Ecosystem Program in Increasing the Performance of the National Logistics System, Improving the Investment Climate, and Increasing the Competitiveness of the National Economy - Arimbhi, Pebriana; Agustina, Dwi; Rahmi, Notika (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Indonesia is one of the countries with the largest logistics costs in ASEAN. In this regard, the government needs to take strategic steps. One of them is the issuance of Presidential Instruction Number 5 of 2020 which is then used as the legal basis for the establishment of a national logistics ecosystem digital platform or National Logistic Ecosystem (NLE). This policy is the responsibility of the General Directorate of Customs and Excise under the supervision of the Indonesian Ministry of Finance. The objective of this research was to analyze the implementation of the NLE program in terms of increasing the performance of the national logistics system, improving the investment climate, and increasing the competitiveness of the national economy in Indonesia. The research method used was qualitative with a descriptive approach. The results of this study indicated that of the six dimensions that were used as benchmarks, four dimensions had worked well. Only two dimensions were not going well. They were the dimension of implementers’ attitude and the dimension of communication. This was due to ongoing planning and policies that still needed to be disseminated more widely. By having the NLE platform, it would certainly increase the performance of the National logistics system, improve the investment climate, and increase the competitiveness of the National economy in Indonesia.